CaPTure: Calcium PeakToolbox for analysis of in vitro calcium imaging data. - Tippani, Madhavi; Pattie, Elizabeth A.; Davis, Brittany A.; Nguyen, Claudia V.; Wang, Yanhong; Sripathy, Srinidhi Rao; Maher, Brady J.; Martinowich, Keri; Jaffe, Andrew E.; Page, Stephanie Cerceo (BMC Neuroscience, 2022)
Background: Calcium imaging is a powerful technique for recording cellular activity across large populations of neurons. However, analysis methods capable of single-cell resolution in cultured neurons, especially for cultures derived from human induced pluripotent stem cells (hiPSCs), are lacking. Existing methods lack scalability to accommodate high-throughput comparisons between multiple lines, across developmental timepoints, or across pharmacological manipulations.Results: To address this need we developed CaPTure, a scalable, automated Ca2+ imaging analysis pipeline ( https://github.com/LieberInstitute/CaPTure ). CaPTuredetects neurons, classifies and quantifies spontaneous activity, quantifies synchrony metrics, and generates cell- and network-specific metrics that facilitate phenotypic discovery. The method is compatible with parallel processing on computing clusters without requiring significant user input or parameter modification.Conclusion: CaPTure allows for rapid assessment of neuronal activity in cultured cells at cellular resolution, rendering it amenable to high-throughput screening and phenotypic discovery. The platform can be applied to both human- and rodent-derived neurons and is compatible with many imaging systems.